The handbook of adult and continuing education - Rocco, Tonette S., 1954-; Smith, M. Cecil; Mizzi, Robert C., 1973-; Merriweather, Lisa R.; Hawley, Joshua D. (Stylus Publishing, LLC., 2021)
"Colleges and universities are increasingly becoming significant sites for adult education scholarship-in large part due to demographic shifts. With fewer U.S. high school graduates on the horizon, higher education institutions will need to attract "non-traditional" (i.e., older) adult learners to remain viable, both financially and politically. There is a need to develop a better corpus of scholarship on topics as diverse as, what learning theories are useful for understanding adult learning? How are higher education institutions changing in response to the surge of adult students? What academic programs are providing better learning and employment outcomes for adults in college? Adult education scholars can offer much to the policy debates taking place in higher education. A main premise of this handbook is that adult and continuing education should not simply respond to rapidly changing social, economic, technological, and political environments across the globe, but should lead the way in preparing adults to become informed, globally-connected, critical citizens who are knowledgeable, skilled, and open and adaptive to change and uncertainty"- Resumé vydavatel